2018
DOI: 10.1038/s41598-018-32423-0
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal administration of resveratrol successfully prevents lung cancer in A/J mice

Abstract: Lung cancer is the most lethal cancer in the world. About 80% of lung cancer deaths are linked to tobacco use. As a complement to tobacco control, efficient chemoprevention strategies are needed to tackle lung cancer epidemic. Resveratrol is one of the most studied natural products, notably for its cancer chemoprevention properties. However, its low oral bioavailability has often limited the translation of in vitro activities to in vivo effects. While oral administration of resveratrol effectively inhibited co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 38 publications
(35 reference statements)
1
20
0
3
Order By: Relevance
“…delivery of CAT. This is a very apparent observation via nose to lungs targeted potential ( Monteillier et al, 2018 , Dao et al, 2018 , Worth et al, 2000 , Jin et al, 2019 ).
Fig.
…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…delivery of CAT. This is a very apparent observation via nose to lungs targeted potential ( Monteillier et al, 2018 , Dao et al, 2018 , Worth et al, 2000 , Jin et al, 2019 ).
Fig.
…”
Section: Resultsmentioning
confidence: 90%
“…Now a drays, various research scientists are targeting the drugs via nose–to–lungs that showed different types of useful applications like avoid hepatic first pass metabolism and non-invasive route with easy to application of drugs ( Monteillier et al, 2018 , Dao et al, 2018 , Worth et al, 2000 , Jin et al, 2019 ). Therefore, these PLGA-NPs.…”
Section: Introductionmentioning
confidence: 99%
“…Monteillier and others (Monteillier et al, 2018) showed that intranasal administration of 60 mg/kg resveratrol to mice with induced lung cancer caused a notable decrease in the tumor multiplicity and volume via enhanced apoptosis. Moreover, treating gastric cancer cells with resveratrol elevated the levels of pro-apoptotic proteins such as Bax, while the levels of anti-apoptotic proteins such as Bcl-2 were decreased compared to untreated controls .…”
Section: Anti-cancer Activitymentioning
confidence: 99%
“…A 25-day in vivo study in A/J mice lung carcinogenesis model demonstrated 27% reduction in tumor multiplicity with 45% lower tumor volume confirming the efficacy of the developed formulation. Such a formulation approach is anticipated to enhance the drug bioavailability and hence has great potential in future clinical studies (Monteillier et al, 2018). In another study, lipid nanoparticles (NPs) of three chemopreventive drugs N-acetyl-L-cysteine, phenethyl isothiocyanate, and resveratrol were developed and their chemopreventive potential was assessed in bronchial epithelial cells.…”
Section: Lung and Bronchial Cancermentioning
confidence: 99%